45 Leptin-LEPR-Desert Hedgehog Signaling Induced Leydig Stem Cells Differentiation in Testis is Modulated by EMT Inducing Transcription Factors which Binds to LEPR. Issue 1 (1st April 2022) - Seetharam, D; Khodamoradi, K; Catherine, II; Farber, N; Parmar, M; Ramasamy, R; Arora, H
ABSTRACT: Introduction: Leydig cells (LCs) are the primary source of testosterone (T) in men, and their dysfunction can lead to T deficiency. The growth and differentiation of LCs is influenced by the paracrine factors released by the testicular microenvironment (TME). Leptin is a 16-kDa protein produced primarily by adipose tissue and exerts a significant influence on hormonal regulation. In our recent study, we demonstrated that Leptin, a paracrine factor secreted by TME, is critical for Leydig stem cell (LSCs) differentiation and subsequent T production under the regulation of the desert hedgehog signaling pathway. Objective: To gain an in-depth understanding of mechanisms that derive the Leptin secretion and decide the fate of LCs are still unclear and is the focus of the present study. Methods: A total of 13 men with testicular failure underwent testis biopsies. The testicular cells were characterized using Flow cytometry, Immunostaining and RNA sequencing then the cells were also treated with Leptin in a dose dependent (0, 1, 10 ng/mL respectively) and time dependent (24, 48, 72, and 96 hours) manner. For the functional studies, UCSC genome browser was used to study the transcription factor genes (TFs) binding the leptin receptor (LEPR) promoter. The list of TFs was subjected to enrichment analysis. To evaluate the effects of shortlisted TFs on leptin-LEPR-DHH to induce EMT in LSCs, qPCR and western blotting were performed. For statistical analysis GraphPad Prism was used. For statistical analysis GraphPad Prism was used. All data were presented as the means ± SEM. All data were presented as the means ± SEM. Results: UCSC Genome browser revealed over 50 TFs, which were subjected to enrichment analysis using ENRICHR. Output revealed TFs; SOX2, SOX8 and SOX9 that were enriched for mechanisms influencing hormonal regulation via hypothalamic pituitary gonadal axis. The role of these TFs has been well established in epithelial to mesenchymal transition in different cancer types, however their impact on LSC differentiation remained underexplored. RNA sequencing data from cells exposed to different concentrations of Leptin showed an inducing effect of Leptin on SOX2, SOX8, Sox9 respectively. This was confirmed at RNA as well as at protein levels. Consequently, upon inhibition of LEPR, the expression of SOX2, SOX8 and SOX9 was reduced as well. Moreover, leptin treatment in conjunction with SOX2, SOX8 and SOX9 was found to modulate epithelial to mesenchymal transition in LCs. Conclusions: Our results demonstrate that Leptin-LEPR-DHH induced Leydig stem cells differentiation in testis is modulated by EMT inducing transcription factors which binds to LEPR. Further studies are ongoing to explore the potential therapeutic effects of leptin treatment in improving fertility. Financial Support: Supported by the Clinician Scientist Development award from American Cancer Society to RR and Research Scholar Award from American Urological Association to HA. J.M.H. is supported by NIH grants 1R01 HL137355, 1R01 HL107110, 1R01 HL134558, 5R01 CA136387, 5UM1 HL113460 and Soffer Family Foundation Disclosure: No